Implementation of Moodle in Physics Learning: Systematic Literature Review - Muslimin Boma; Heru Kuswanto; Rida Siti Nur’aini Mahmudah; Diki Chen; Novita Eka Putri; Santri Adi Putri (Jurnal Penelitian Pendidikan IPA, 2023)
This systematic review study aims to determine Moodle e-learning in physics learning in terms of nationally published journals. This type of research is a systematic review study using the Prisma model. The dominant research methodology is quantitative research with descriptive statistical analysis. The findings in this study are that the author of many articles contains Research & Development (R&D) research on physics learning devices, the distribution of authors and institutions is uneven, and the data obtained is in the form of numbers. Data analysis was performed manually and using Vosviewer software. Data analysis that was done manually included: SINTA level, year, author, institution, use of Moodle, keywords, samples based on educational level, type of research, and data analysis in the research of each article. The results of the article review show that the use of Moodle e-learning is more widely used in the development of teaching materials than used in classroom learning experiments. So it can be concluded that the need for learning development by utilizing the Moodle platform so that learning is more meaningful and enjoyable is not only used only for physics learning training.